2014
DOI: 10.1007/s12253-014-9861-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Certain Leukemia/Lymphoma Related microRNAs and its Correlation with Prognosis in Childhood Acute Lymphoblastic Leukemia

Abstract: In spite of the improved efficacy of therapy, it still fails in 15-20 % of childhood acute lymphoblastic leukemia (ALL) patients. Recently, altered expression of certain miRNAs (miRs) have been described in ALL with potential effect on prognosis. Presence of certain miRs (miRNA-16, -21, -24, -29b, -128b, -142-3p, -155, -223) was characterized in human lymphoma and leukemia cells by real-time PCR. Expression of miRs in pediatric ALL patients (n = 24) was measured before chemotherapy, at conventional response ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…In both the test (p = 0.039) and validation (p = 0.037) cohorts, Mei et al [48] observed that the incidence of relapse or induction failure was higher in patients who had a lower expression of miR-210. Nemes et al [49] evaluated the expression of eight miRNAs (miR-16, miR-21, miR-24, miR-29b, miR-128b, miR-142-3p, miR-155, and miR-223) and their association with relapse and reported that overexpression of miR-128b and downregulation of miR-223 were associated with relapse.…”
Section: Dna Methylationmentioning
confidence: 99%
“…In both the test (p = 0.039) and validation (p = 0.037) cohorts, Mei et al [48] observed that the incidence of relapse or induction failure was higher in patients who had a lower expression of miR-210. Nemes et al [49] evaluated the expression of eight miRNAs (miR-16, miR-21, miR-24, miR-29b, miR-128b, miR-142-3p, miR-155, and miR-223) and their association with relapse and reported that overexpression of miR-128b and downregulation of miR-223 were associated with relapse.…”
Section: Dna Methylationmentioning
confidence: 99%
“…To the extent that miRNAs control the expression of protein-coding genes,18 regulate many biological pathways,15 are involved in disease prognosis,21 provide resistance to disease,22 and are predictors of relapse,23 this is a significant finding. Importantly, WBC is a well-known, strong, and independent predictor of both relapse and disease prognosis,8 which have also been associated with miRNAs 2123. Therefore, discovery of miRNAs that are potentially involved in regulating genes modulating WBC could have significant impact in improving treatment protocols and development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in cases of ALL, the expression pattern of specific miRNAs has been associated not only to the diagnosis but also to the prognosis and response to therapy. For example, miR-92a overexpression correlated with worse outcomes [135] while high miR-128b was associated with a better prognosis and response to corticosteroid treatments (Prednisolone) [136].…”
Section: Mirna: a Factor In Multifactorial Diseasesmentioning
confidence: 99%